Saint John at Calvary: technical and material study of a polychrome wood sculpture - Helena Pereira (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
A polychrome wood sculpture depicting Saint John at Calvary, probably a 17th century Portuguese production, was the subject of a study that aimed to characterise its materials and techniques. Radiography, optical microscopy, scanning electron microscopy, Fourier transform infrared spectroscopy and Raman spectroscopy were used. Some unusual characteristics have been detected, like the employment of wood with some imperfections and, specially, the use of brochantite and antlerite as pigments.